Aeolian dust emission, transport and deposition in Western Libya - Elatrash, Mokhtar Salem (2004)
Of numerous aeolian studies around the world, few have been dedicated to dust trapping in the Saharan regions and none is known in Libya. This research aims to explore the extent of dust activities in the western part of Libya, the main factors that influence dust entrainment and deposition, the likely regional emission sources transporting aerosol to this part of the country and ultimately to establish base line information in space and time based on a study area larger than the size of the UK. Dust trapping was carried out at thirty sites on a monthly basis starting from the beginning June 2000 until the end of May 2001. A physical characterization of 274 aeolian sediments were based on grain size distribution analysis and the mineral composition was based on XRD testing of 24 dust samples taken from extreme locations near the Mediterranean Sea and about 800 km inland.